1991
DOI: 10.1017/s0033291700014653
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive abnormalities in multiple sclerosis: a psychometric and MRI study

Abstract: SYNOPSISThis study reports the cognitive abnormalities of a group of 58 patients with definite multiple sclerosis (MS). The psychometric functions measured were: '1Q deficit', verbal and visual memory, abstracting ability, visual and auditory attention and naming ability. The presence of brain pathology was investigated using magnetic resonance imaging (MRI). A group of 46 physically disabled controls without significant brain disease was used for comparison. Normative MRI data were obtained from a group of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 37 publications
2
50
0
4
Order By: Relevance
“…Previous studies have already found that duration of the disease and physical disability are not strictly linked with the cognitive functioning of these patients [6][7][8][9][10]20]. This lack of correlation is partly not surprising, since EDSS reflects mainly cerebellar, brainstem and spinal cord involvement.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies have already found that duration of the disease and physical disability are not strictly linked with the cognitive functioning of these patients [6][7][8][9][10]20]. This lack of correlation is partly not surprising, since EDSS reflects mainly cerebellar, brainstem and spinal cord involvement.…”
Section: Resultsmentioning
confidence: 87%
“…Although psychopathological symptoms in multiple sclerosis have been known since the early descriptions of the disease and mental functions in MS were investigated in some detail already almost 90 years ago (e. g. [51]), essential contributions to the understanding of cognitive deficits were made in the last five decades (e. g., [12,50] ■ Abstract Neuropsychological dysfunctions have been well documented in patients with multiple sclerosis. We herein give an overview of the main findings of recent decades.…”
Section: Neuropsychology Of Multiple Sclerosismentioning
confidence: 99%
“…The cognitive domains most commonly impaired are memory, attention, information processing, executive function, and visuospatial abilities (Rao et al, 1991a;Ron et al, 1991). The pathophysiology of neuropsychological (NP) deficits is, at least partially, unclear.…”
Section: Introductionmentioning
confidence: 99%